Bioenergetics of aerobic and anaerobic growth of Shewanella putrefaciens CN32 - Wray, Addien C.; Gorman-Lewis, Drew (Frontiers in Microbiology, 2023)
Shewanella putrefaciens is a model dissimilatory iron-reducing bacterium that can use Fe (III) and O 2 as terminal electron acceptors. Consequently, it has the ability to influence both aerobic and anaerobic groundwater systems, making it an ideal microorganism for improving our understanding of facultative anaerobes with iron-based metabolisms. In this work, we examine the bioenergetics of O 2 and Fe(III) reduction coupled to lactate oxidation in Shewanella putrefaciens CN32. Bioenergetics were measured directly via isothermal calorimetry and by changes to the chemically defined growth medium. We performed these measurements from 25 to 36 • C. Modeling metabolism with macrochemical equations allowed us to define a theoretical growth stoichiometry for the catabolic reaction of 1.00 O 2 :lactate and 1.33 Fe(III):lactate that was consistent with the observed ratios of O 2 :lactate (1.20±0.23) and Fe(III):lactate (1.46±0.15) consumption. Aerobic growth showed minimal variation with temperature and minimal variation in thermodynamic potentials of incubation. Fe(III)-based growth showed a strong temperature dependence. The Gibbs energy and enthalpy of incubation was minimized at ≥30 • C. Energy partitioning modeling of Fe(III)-based calorimetric incubation data predicted that energy consumption for non-growth associate maintenance increases substantially above 30 • C. This prediction agrees with the data at 33 and 35 • C. These results suggest that the effects of temperature on Shewanella putrefaciens CN32 are metabolism dependent. Gibbs energy of incubation above 30 • C was 3 -5 times more exergonic with Fe(III)-based growth than with aerobic growth. We compared data gathered in this study with predictions of microbial growth based on standard-state conditions and based on the thermodynamic efficiency of microbial growth. Quantifying the growth requirements of Shewanella putrefaciens CN32 has advanced our understanding of the thermodynamic constraints of this dissimilatory iron-reducing bacterium.